2011
DOI: 10.1556/achrom.23.2011.2.7
|View full text |Cite
|
Sign up to set email alerts
|

Development and validation of a stability-indicating HPTLC assay method for idebenone

Abstract: A simple, selective, precise, and stability-indicating high-performance thin layer chromatographic (HPTLC) method has been established and validated for the analysis of idebenone in bulk drug and formulations. The compounds were analyzed on aluminum-backed silica gel 60 F 254 plates with petroleum ether-methanol (4:1, v/v) as mobile phase. Densitometric analysis of idebenone was performed at 282 nm. Regression analysis data for the calibration plots were indicative of good linear relationship between response … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 7 publications
0
2
0
Order By: Relevance
“…Stability studies are essential to know the effect of storage conditions of a galenic product to determine the appropriate shelf life and storage conditions [14]. The International Conference on Harmonization (ICH) [15] suggests that analytical test procedures for stability samples should be fully validated [16]. There are reported methods for the determination of ubiquinones by HPLC-UV-vis [4,17,18], colorimetric methods [19], HPTLC [16], and, finally, GC-MS or LC-MS [3,16,20].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Stability studies are essential to know the effect of storage conditions of a galenic product to determine the appropriate shelf life and storage conditions [14]. The International Conference on Harmonization (ICH) [15] suggests that analytical test procedures for stability samples should be fully validated [16]. There are reported methods for the determination of ubiquinones by HPLC-UV-vis [4,17,18], colorimetric methods [19], HPTLC [16], and, finally, GC-MS or LC-MS [3,16,20].…”
Section: Introductionmentioning
confidence: 99%
“…The International Conference on Harmonization (ICH) [15] suggests that analytical test procedures for stability samples should be fully validated [16]. There are reported methods for the determination of ubiquinones by HPLC-UV-vis [4,17,18], colorimetric methods [19], HPTLC [16], and, finally, GC-MS or LC-MS [3,16,20]. LC-MS appears to be the gold standard for sta-bility studies of pharmaceutical preparations thanks to the ability to quantify analytes in solution, and to the high sensitivity and reproducibility inherent of MS. A fully validated HPLC-MS/MS method has been applied but for pharmacokinetic study [3] in plasma and urine samples to detect IDB and metabolites as reported above.…”
Section: Introductionmentioning
confidence: 99%